PEMANFAATAN MEDIA KALENDER DALAM MENUMBUH KEMBANGKAN KEMAMPUAN MEMBACA, MENULIS DAN BERHITUNG (CALISTUNG) PADA PENDIDIKAN ANAK USIA DINI KHALIFAH TASYKURI KABUPATEN KAUR - Yuli Handayani (IAIN Bengkulu, 2019)
This research is background because, limited ability to read writing, and count the. in the bThis can be seen based on the preliminary observations researchers that the learning activities teachers do not use media learning that the kid looks not actively participate in learning, as read writing, and count.This study attempts to find out the uses of the media a calendar and the manner of capitalize on the fact that the media was said were figure brought the calendar in may have developed he can read and , would be willing to write, and arithmetic (calistung) on development for early childhood education of a caliph tasykuri village their folds and pastures and long kec.Semidang Gumay Kabupaten Kaur.The kind of research writer is provided by way of research the act of a class of.Analysis techniques of the data that the funds should be used in this research is a technique descriptive of qualitative and quantitative, That is by establishing a snapshot of the and you do that by exposure to/ cereal offering the data, using formulas simple and the withdrawal of a conclusion. The analysis of the data indicates that: 1. The use of media can develop calendar were ability to read , writing and arithmetic (calistung) in early childhood education successors tasykuri: a) on pre cycle rata-rata namely the score 66.57 with completeness learning klasikal of 14,29% with kriterian very low. b) cycle 1 meeting on 1 increased to value rata-rata score of 71,43 with completeness learn classical of 28,57% on low. c) on cycle 2 meeting 1, increased worth rata-rata score namely 81.14 withcompletenessclassical of 42,86 %, on low. d) cycle 2 meeting on 2 enhanced worth rata-rata score namely 86,29 with completeness learn classical of 85.71% on very high . e) cycle 2 meeting on 2 more up with the score the rata-rata 87,5, with ketuntasan klasikal of 92,85% on very high.2. How to use the in media were developed ability to read, writing, and count (calistung) in early childhood education successors tasykuri:a) teacher media suspend the calendar on board that disesuiakan at the height of students. b) learners match pictures by means of put the same exact in a media calendar, c) learners put a picture conforming to the existing in a media calendar. The results of comparison of utilization of calendar media in developing the ability of reading, writing, and counting between cycle I and cycle II has increased significantly and has reached the target of learning mastery by 80%.